Prevalence and associated risk factors of chronic malnutrition amongst children under five in Eswatini - Glorious H. Dlamini; Boikhutso Tlou (AOSIS, 2022)
Background: About 20 million children under fi-ve in Southern Africa have chronic malnutrition. This study determines the prevalence of chronic malnutrition and associated risk factors amongst children under five. Aim: To determine the proportion of children with chronic malnutrition and investigate associated risk factors of chronic malnutrition. Setting: The study was conducted in communities in the four regions of Eswatini. Methods: This study is a retrospective cross-sectional study that used data from a Multiple Indicator Cluster Survey (MICS) conducted in 2014. The study involved 3261 children who are under 5 years of age. Data on nutritional status and household characteristics were used. Logistic regression was used to identify factors associated with chronic malnutrition in the univariable and multivariable models, respectively. Results: Results showed that 18.1% (confidence interval [CI]: 18.5-21.5) of children under five have chronic malnutrition. The highest prevalence was 20.8% (CI: 17.4-24.7) in the Shiselweni region, followed by the Manzini region with 17.6% (CI: 14.5-21.1) and the Lubombo region with 17.2% (CI: 13.9-21.2). The lowest prevalence of chronic malnutrition at 16.7% (CI: 13.6-20.3) was the Hhohho region. The results indicated that low birth weight (odds ratio [OR] = 4.63, CI: 1.12-19.2), mothers' lack of education (OR = 1.50, CI: 1.04-2.17) and children aged 12-24 months (OR = 1.28, CI: 0.88-1.87) were significantly associated with chronic malnutrition. Conclusion: The findings showed that malnutrition is an important public health problem in children under five and needs a multisectoral response. Low birth weight, mothers' education and the child's age are risk factors associated with chronic malnutrition. Contribution: The results inform evidence-based programming for the prevention of chronic malnutrition in children thus assist the country to meet sustainable development goals.